2021
DOI: 10.1002/alz.12348
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical impact of the AT(N) framework on dementia using a community autopsy sample

Abstract: The AT(N) research framework categorizes eight biomarker profiles using amyloid (A), tauopathy (T), and neurodegeneration (N), regardless of dementia status. We evaluated associations with dementia risk in a community‐based cohort by approximating AT(N) profiles using autopsy‐based neuropathology correlates, and considered cost implications for clinical trials for secondary prevention of dementia based on AT(N) profiles. We used Consortium to Establish a Registry for Alzheimer's Disease (moderate/frequent) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…4,5 According to the biological definition of AD 6 and recent reports, [7][8][9][10] Aβ (A) pathology presents initially in disease onset, followed by tau (T) aggregation, which subsequently results in neurodegeneration (N) and cognitive decline. However, several recent studies [11][12][13] also identified different A/T/N profiles with overlapping features of neurodegeneration and cognitive decline, indicating we may need extra techniques beyond A/T/N biomarkers to understand the progression of the disease fully. 14 Synaptic impairment appears closely linked to neurodegeneration and cognitive decline in AD.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 According to the biological definition of AD 6 and recent reports, [7][8][9][10] Aβ (A) pathology presents initially in disease onset, followed by tau (T) aggregation, which subsequently results in neurodegeneration (N) and cognitive decline. However, several recent studies [11][12][13] also identified different A/T/N profiles with overlapping features of neurodegeneration and cognitive decline, indicating we may need extra techniques beyond A/T/N biomarkers to understand the progression of the disease fully. 14 Synaptic impairment appears closely linked to neurodegeneration and cognitive decline in AD.…”
Section: Introductionmentioning
confidence: 99%